Advances in Wireless Communications and Applications Smart Communications: Interactive Methods and Intelligent Algorithms, Proceedings of 3rd ICWCA 2019 - Kountchev, Roumen; Mahanti, Aniket; Chong, Shen.; Patnaik, Srikanta; Favorskaya, Margarita; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2021)
This book features selected papers presented at the 3rd International Conference on Wireless Communications and Applications (ICWCA 2019), held at Hainan University, China. Focusing on applications of the latest smart theories and approaches, and recent advances in the field, it covers topics such as OFDM and multi-carrier techniques; smart antenna and space-time signal processing; MIMO, multi-user MIMO, and massive MIMO; modulation, coding, and diversity techniques; dynamic spectrum access and cognitive radio; interference management and radio resource allocation; equalization techniques; synchronization, estimation, and detection techniques; and wireless multiple access (e.g. CDMA, OFDMA, NOMA, ). .
Chapter 1. A Novel Low Complexity Orthogonalization Method -- Chapter 2. Research on Radio Base Station Distribution Technology in Transrapid System Communication -- Chapter 3. A Novel Node Scheduling Algorithm for Solar-Powered Wireless Sensor Networks -- Chapter 4. A USRP-Based Testbed of Multi-Agent Reinforcement Learning for Dynamic Spectrum Anti-Jamming -- Chapter 5. Improved DOA-Matrix Method for Two Parallel Uniform Linear Array -- Chapter 6. UKF Applied in Target Tracking Based on Single Observation Station -- Chapter 7. Research on handover Strategy Based on Greedy Algorithm in Vehicle Edge Computing -- Chapter 8. Safety Analysis Method Considering Cascading Trips Based on Particle Swarm Optimization -- Chapter 9. A Method for Restraining Cascading Trip Based on Node Power -- Chapter 10. Improved Window Decoding of Spatially Coupled LDPC Codes.
Keywords: Wireless communication systems; Mobile communication systems; Electrical engineering; Computer communication systems; Computer networks -- Security measures; Wireless and Mobile Communication; Communications Engineering, Networks; Computer Communication Networks; Mobile and Network Security